Bideshika Lagi Nepali Bhasha Shikshyanma Shikshkako Dayitwa - Acharya, Krishna Prasad (Tribhuvan University Journal, 2011)
Available with fulltext. Key words: Nepali Language; Foreigner; Teachers' role; Nepal Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 147-154 Uploaded date: 29 April, 2011